Virulence spectrum, molecular characterisation and fungicide sensitivity of the South African Rhynchosporium secalis population - Robbertse, Barbara (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDAgric)--University of Stellenbosch, 2000.